Nasal Administration of Dolutegravir Loaded Nanoparticles Based Mucoadhesive in situ Gel: Design and in vivo Assessment - Sreeharsha, Nagaraja; Cherukuri, Sandhyanjali; Naveen, Nimbagal Raghavendra; Goudanavar, Prakash; Fattepur, Santosh; Aldhubiab, Bandar; Almuqbil, Rashed M; Nair, Anroop B (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: To assess the potential for targeting the brain through intranasal delivery, this study focuses on optimizing and developing a mucoadhesive in situ gel formulation containing Dolutegravir nanoparticles. Materials and Methods: Employing a central composite design, the study optimized the concentration of variables of Hydroxypropyl methylcellulose (HPMC, X1) and Poloxamer 407 (X2) on the gelation temperature (Y1) and drug release (Y2). The optimized drug loaded nanoformulations were assessed for various pharmaceutical features, in vitro release and evaluated in vivo. Results: Both variables significantly impacted the responses (p<0.05). The selected formulation displayed beneficial rheological characteristics and prolonged drug release. In vivo pharmacokinetic analysis in rats post-intranasal administration of the optimized in situ gel demonstrated markedly higher (p<0.0001) Cmax (2-fold) and AUC0-t (3-fold) values in the targeted brain tissue as compared to intravenous administration. Reduced Dolutegravir exposure in the central compartment validates limited absorption with nasal therapy. Conclusion: The study affirms the potential of the in situ mucoadhesive nasal gel in delivering Dolutegravir to the brain. Thus, the optimized nasal gel emerges as a promising therapeutic alternative for Neuro AIDS by efficiently delivering Dolutegravir to the brain.
Keywords: Dolutegravir; in situ gel; Nasal route; Brain; in vivo